Sports atmosphere and psychological resilience in college students: mediating role of growth mindset - Zhang, Weijie; Li, Jingjing (Frontiers in Psychology, 2025)
IntroductionThe mental health of college students has garnered increasing attention currently, and psychological resilience is recognized as a crucial factor in coping with pressure and challenges. However, the influencing factors of psychological resilience require further exploration. This study aims to investigate the relationship between sports atmosphere and psychological resilience among college students, as well as the mediating role of a growth mindset.MethodsA questionnaire survey was conducted with 315 college students using the Outdoor Sports Atmosphere Scale, Growth Mindset Scale, and Brief Resilience Scale.ResultsThe findings revealed significant positive correlations between sports atmosphere, growth mindset, and psychological resilience. Regression analysis showed that a positive sports atmosphere significantly predicted both psychological resilience (β = 0.371, t = 8.648, p < 0.01) and growth mindset (β = 0.462, t = 10.227, p < 0.01). Structural equation modeling further confirmed that growth mindset played a significant mediating role in the relationship between sports atmosphere and psychological resilience [β = 0.182, 95% CI (0.036, 0.189), p < 0.05].DiscussionThese results highlight the importance of a supportive sports atmosphere in fostering psychological resilience among college students, with growth mindset acting as a key intermediary factor. By cultivating a growth mindset, students may better translate the benefits of an encouraging sports atmosphere into improved psychological resilience and adaptability. These insights provide actionable strategies for educators and policymakers to design interventions that promote psychological wellbeing.